(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2014)
Very little is known about the immediate response of nebulized corticosteroid in addition to systemic steroids plus nebulized salbutamol in the early management of acute asthma in children. This study was aimed to observe any immediate effect of nebulized budesonide in the management of acute asthma in children. A total of 106 asthmatic patients aged between 5-12 years were investigated in a prospective single-blind, placebo controlled fashion. All subjects were entered in a randomized manner into one of two groups, Group-1 (Study Group) and Group-II (Control Group). After the Paediatric Asthma Severity Score (PASS) and the Peak Expiratory Flow Rates (PEFR) had been measured in all patients at the beginning of the study, both the study group (Group-1) and the control group (Group-II) received three consecutive doses of nebulized salbutamol (0.15 mg/kg/dose) and one dose of parenteral hydrocortisone (5 mg/kg/dose, intravenous). After this initial treatment, nebulized budesonide (1 mg/dose) was administered to patients in Group-1. One hour latter, the PASS and the PEFR were measured once more and at discharge, the durations of hospital stay (in days) were recorded for comparison between two groups. There were 53 patients in Group-1 (mean age: 7.99€2.12) and 53 patients in Group-II (mean age: 7.45+2.13). Both the groups were comparable for age (p=0.212) and sex (p=0.242)and inhaled steroid prophylaxis rate (p=0.233). No statistically significant difference was detected between the two groups with respect to the decrease in PASS (p=0.851). Yet, there were statistically significant differences between the two groups with respect to the increase in PEFR (p=0.006) and durations of hospital stay in days (p=0.004). The positive immediate effect of nebulized budesonide in addition to systemic steroids and nebulized salbutamol in improving the PEFR as well as durations of hospital stay in asthmatic children is an encouraging finding for further study of its routine use in the paediatric emergency department. JCMCTA 2014 ; 25 (1): 27-31